Prototipos arquitectónicos carcelarios como medios para la resocialización en las cárceles de Colombia (2022)
At the national level, it is possible to show that prisons and penitentiaries are not physically prepared to house the inmate population in intramural facilities, which also do not offer habitability conditions and do not meet the main objective of imprisonment, which is the re-socialization of persons deprived of their liberty. The objective of this project is the investigation and study of the causes and variables that influence the habitability conditions and the processes of resocialization of persons deprived of liberty (PPL), in order to establish design parameters that allow the spatial configuration of prison architectural prototypes, with the intention of providing solutions as to how a space is inhabited and used, it should also be said that they are proposed in order to be applied and replicated in various prison environments, under concepts and guidelines found throughout the research.